Atherosclerosis Linked to Aberrant Amino Acid Metabolism and Immunosuppressive Amino Acid Catabolizing Enzymes - Zaric, Bozidarka L.; Radovanovic, Jelena N.; Gluvic, Zoran; Stewart, Alan J.; Essack, Magbubah; Motwalli, Olaa; Gojobori, Takashi; Isenovic, Esma R. (Frontiers in Immunology, 2020)
Cardiovascular disease is the leading global health concern and responsible for more deaths worldwide than any other type of disorder. Atherosclerosis is a chronic inflammatory disease in the arterial wall, which underpins several types of cardiovascular disease. It has emerged that a strong relationship exists between alterations in amino acid (AA) metabolism and the development of atherosclerosis. Recent studies have reported positive correlations between levels of branched-chain amino acids (BCAAs) such as leucine, valine, and isoleucine in plasma and the occurrence of metabolic disturbances. Elevated serum levels of BCAAs indicate a high cardiometabolic risk. Thus, BCAAs may also impact atherosclerosis prevention and offer a novel therapeutic strategy for specific individuals at risk of coronary events. The metabolism of AAs, such as L-arginine, homoarginine, and L-tryptophan, is recognized as a critical regulator of vascular homeostasis. Dietary intake of homoarginine, taurine, and glycine can improve atherosclerosis by endothelium remodeling. Available data also suggest that the regulation of AA metabolism by indoleamine 2,3-dioxygenase (IDO) and arginases (1 and 2) are mediated through various immunological signals and that immunosuppressive AA metabolizing enzymes are promising therapeutic targets against atherosclerosis. Further clinical studies and basic studies that make use of animal models are required. Here we review recent data examining links between AA metabolism and the development of atherosclerosis.